Determinants of transfer pricing agressiveness: Empirical evidence from Australian firms - Richardson, G.; Taylor, Grantley; Lanis, R. (Elsevier Ltd, 2013)
This study examines the major determinants of transfer pricing aggressiveness. Based on a hand-collected sample of 183 publicly-listed Australian firms for the 2009 year, our regression results show that firm size, profitability, leverage, intangible assets, and multinationality are significantly positively associated with transfer pricing aggressiveness after controlling for industry-sector effects. Our additional regression results also indicate that firms augment their transfer pricing aggressiveness through the joint effects of intangible assets and multinationality.